Adiponectin predicts poor response to antidepressant drugs in major depressive disorder. (4th May 2021) - Benedetti, Francesco; Branchi, Igor; Poletti, Sara; Lorenzi, Cristina; Bigai, Giorgia; Colombo, Cristina; Zanardi, Raffaella
Abstract: Objective: Produced by adipocytes, adiponectin crosses the blood‐brain barrier to bind with specific receptors in the hypothalamus, brainstem, hippocampus, and cortex. In patients with major depressive disorder (MDD), circulating levels of adiponectin inversely related with antidepressant response to ketamine, and predicted a better response to multi‐target drug combinations than to escitalopram. We investigated the effect of adiponectin on response to antidepressants in a naturalistic setting. Methods: We assessed baseline plasma levels of adiponectin in 121 MDD inpatients, treated with antidepressant drug monotherapy based on clinical need (selective serotonin reuptake inhibitors, venlafaxine, duloxetine) in a specialized hospital setting. Severity of depression was weekly assessed with Hamilton scale ratings. Results: Adiponectin plasma levels were higher in patients with MDD compared with healthy controls, and negatively influenced the pattern of antidepressant response (higher baseline levels, worse response) independent of the drug class and of the baseline severity of depression, and of age, sex, and body mass index. Conclusions: The identification of adiponectin as a predictor of antidepressant response to drugs of different mechanism of action, such as ketamine, SSRIs, and SNRIs, and both in experimental and in clinical settings, warrants interest for further study of its pathways to search for novel biomarkers and therapeutic targets.